2021
DOI: 10.3389/fimmu.2021.790574
|View full text |Cite
|
Sign up to set email alerts
|

Immunometabolites Drive Bacterial Adaptation to the Airway

Abstract: Pseudomonas aeruginosa and Staphylococcus aureus are both opportunistic pathogens that are frequently associated with chronic lung infections. While bacterial virulence determinants are critical in initiating infection, the metabolic flexibility of these bacteria promotes their persistence in the airway. Upon infection, these pathogens induce host immunometabolic reprogramming, resulting in an airway milieu replete with immune-signaling metabolites. These metabolites are often toxic to the bacteria and create … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 75 publications
0
12
0
Order By: Relevance
“…A component of the TCA cycle generated by Acod1 or Irg1 , itaconate has a well-established role in modulating the proinflammatory response to LPS. Its importance in host defenses against S. aureus is being increasingly appreciated, as this is one of the major metabolites found in the airway in S. aureus pneumonia ( Tomlinson et al., 2021 ). Whilst itaconate suppresses inflammation in the host by inhibiting the NLRP3 inflammasome, glycolytic enzymes and succinate dehydrogenase (SDH/mitochondrial complex II) ( Lampropoulou et al., 2016 ; Qin et al., 2019 ; Hooftman et al., 2020 ), it has several bacterial targets.…”
Section: Immunometabolites Direct S Aureus Adaptat...mentioning
confidence: 99%
See 2 more Smart Citations
“…A component of the TCA cycle generated by Acod1 or Irg1 , itaconate has a well-established role in modulating the proinflammatory response to LPS. Its importance in host defenses against S. aureus is being increasingly appreciated, as this is one of the major metabolites found in the airway in S. aureus pneumonia ( Tomlinson et al., 2021 ). Whilst itaconate suppresses inflammation in the host by inhibiting the NLRP3 inflammasome, glycolytic enzymes and succinate dehydrogenase (SDH/mitochondrial complex II) ( Lampropoulou et al., 2016 ; Qin et al., 2019 ; Hooftman et al., 2020 ), it has several bacterial targets.…”
Section: Immunometabolites Direct S Aureus Adaptat...mentioning
confidence: 99%
“…Whilst itaconate suppresses inflammation in the host by inhibiting the NLRP3 inflammasome, glycolytic enzymes and succinate dehydrogenase (SDH/mitochondrial complex II) ( Lampropoulou et al., 2016 ; Qin et al., 2019 ; Hooftman et al., 2020 ), it has several bacterial targets. Itaconate inhibits the glyoxylate cycle of Salmonella typhimurium and Pseudomonas aeruginosa as well as glycolysis of S. aureus ( McFadden and Purohit, 1977 ; Hersch and Navarre, 2020 ; Tomlinson et al., 2021 ), crucial pathways for the survival of these pathogens. While the former two pathogens can degrade itaconate ( Sasikaran et al., 2014 ; Wang et al., 2019 ), S. aureus lacks these degradative enzymes, yet can tolerate it by actively altering its metabolic activity.…”
Section: Immunometabolites Direct S Aureus Adaptat...mentioning
confidence: 99%
See 1 more Smart Citation
“…With the development of metabolomics, research has revealed itaconic acid is not only present in microorganisms such as fungi but also widely present in mammalian immune cells (especially macrophages), and that it is produced in large quantities in response to external stimuli of inflammation (15). Recent years have also seen an explosion in the study of itaconic acid in macrophages (16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…To survive in the host, P. aeruginosa has evolved multiple means of scavenging nutrients and adjusting its metabolism to maintain growth while also coping with stress ( 14 ). Furthermore, P. aeruginosa secretes an array of surface-associated and extracellular virulence factors to cause disease in the host and interfere with host defense ( 15 ).…”
Section: Introductionmentioning
confidence: 99%